Development of a noncontact heart rate monitoring system for sedentary behavior based on an accelerometer attached to a chair. (16th February 2015) - Lim, Eunho; Lee, Hyo-Ki; Myoung, Hyoun-Seok; Lee, Kyoung-Joung
Abstract: Although people spend a third of their day engaged in sedentary activities, research on heart activity during sitting is almost nonexistent because of the discomfort experienced when electrocardiogram (ECG) measurement electrodes are attached to the body. Accordingly, in this study, a system was developed to monitor heart rate (HR) in a noncontact and unconstrained way while subjects were seated, by attaching an accelerometer on the backrest of a chair. Acceleration signals were obtained three times from 20 healthy adults, a detection algorithm was applied, and HR detection performance was evaluated by comparing the R-peak values from the ECG. The system had excellent performance results, with a sensitivity of 96.10% and a positive predictive value of 96.43%. In addition, the HR calculated by the new system developed in this study was compared with HR calculated using ECG. The new system exhibited excellent performance; its results were strongly correlated with that of ECG ( r = 0.97, p 0.0001; average difference of −0.08 ± 4.60 [mean ± 1.96∙standard deviation] in Bland–Altman analysis). Accordingly, the method presented in this study is expected to be applicable for evaluating diverse autonomic nervous system components in a noncontact and unconstrained way using an accelerometer to monitor the HR of sedentary workers or adolescents.